On a Novel Topology of Matrix Converter Applied to Accelerator DC Power Supply - Bin Wang; Weizhang Song; Yang Si (Complexity)
The current topology schemes of heavy ion accelerator power supply have serious pollution to the power grid caused by low power factor of the grid side. Considering the characteristics of adjustable power factor and bidirectional energy transfer of the matrix converter, the possibility of which applied to the accelerator DC power supply is studied and three kinds of backup topology schemes including the preceding regulated matrix rectifier (MR) are proposed in this article. Given the actual situation of accelerator power supply, research has been focused on the modulation strategy suitable for the topology of the preceding regulated MR and simulation validation. Based on simulation of the preceding regulated MR scheme, a matrix power prototype is developed. A power factor tester is utilized to test grid side power factor. According to the experimental results, it is prospectively feasible to apply the preceding regulated MR topology to accelerator DC power supply, with excellent performance of the grid side.